(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The world is witnessing an unprecedented growth in urban population with huge pressure on infrastructure. Urban transportation is facing challenges of increased trips and thereby growth of vehicles on the streets. Massive infrastructure works of highway construction, road widening, flyovers, MRTS are in progress. A considerable amount of infrastructure development is required to mitigate the surge of increased trips and urban mobility. Heavy construction equipment operate on these sites with diverted traffic during the construction of these infrastructure. Many of these sites are in the residential and commercial built-up areas. At several times abutting land-use are in silence zone (Hospital, Educational institutions, courts). Vehicular traffic is the main source of noise on streets. During construction phase, noise pollution is often associated with operating heavy equipment on site of construction. Several ill effects of constant exposure to noise pollution has been recorded. This research paper examines the temporal variation of Noise level at a double decker fly-over construction site in the city of Patna, India and it’s physiological consequences.